A negociação no processo de escrita colaborativa para a produção de um blog em um curso semipresencial de Espanhol LE - Salotti, Luciana Siqueira Rosseto (2015)
In this research, we aim at describing and understanding negotiation in collaborative writing process in order to produce a blog for a Spanish as a foreign language hybrid course. Theoretically, this study is based on Morin (2004, 2005 e 2010) and Moraes (2008) complexity, and on Santa-Cecilia (1996) and Donnino, Platero and Weigel (2013) mainly in teaching Spanish in Brazil, on among others, Zamel (1992) and Lerner (2002), who describe writing and collaborative writing and others. It is also based on Moraes (2008) and Valentini and Fagundes (2005) concept of negotiation. 9th grade students from a private school inland São Paulo state took part of this study. Besides their regular Spanish classes, they took a hybrid (on line and face-to-face) course which is the object of this study. The texts analyzed here were produced during this extra course. Students had to choose films as subject for the blog to be created by them, so discussions on those texts took place on Moodle and WhatsApp and reflections were written on Moddle s diary. Concerning methodology, we used Ricoeur (1986/2002), van Manen (1990) and Freire (2010/2012a) hermeneutic phenomenology approach. Our investigation showed that the focused phenomenon is built from the topics in the Forum: call, organization and teasing; in WhatsApp: agreement, trick, organization, teasing and complaining; and in the Diary: finding, expectation, anger and prudence. Each tool had its own progress and ramifications